ANALYSIS OF VOLATILE ORGANIC COMPOUNDS IN ROSE PETALS USING HEADSPACE SOLIDPHASE MICROEXTRACTION COUPLED TO GAS CHROMATOGRAPHY-MASS SPECTROMETRY - Eisner, Aleš; Surmová, Silvie; Bajer, Tomáš; Kosová, Tereza; Ventura, Karel (My University, 2017)
Headspace solid-phase microextraction coupled to gas chromatography and mass spectrometry (HS-SPME-GC/MS) has been optimised for the analysis of volatile compounds in six samples of rose petals (Rosa Mariyo, Rose Tara, Rosa Rhodos, Rosa Sudoku, Rosa Deep Purple, Rosa Tacazzi). Volatiles from roses were extracted using a SPME fibre by carrying out the subsequent separation and identification by comparison of their mass spectra with mass spectra libraries and retention indexes. Several factors influencing the SPME were taken into account; namely, extraction time, extraction temperature and the sample weight. The optimal parameters of the extraction of volatile compounds were obtained based on statistical evaluation; the most suitable conditions being the extraction time of 60 min., the extraction temperature of 90 °C and the sample weight of 0.7 g.
Analýza těkavých organických látek ve vzorcích okvětních plátků růží pomocí headspace SPME spojené s GC-MS
Keywords: GC-MS; SPME; rose; volatile compounds